PEGON ARABIC LETTER STYLING IN CREATION OF BATIK MOTIFS ON CASUAL CLOTHING - Della Putri Mutika Windi; Aan Sudarwanto (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
Arabic Pegon is an Arabic script used to write regional languages. The Arabic Pegonscript originates from the Javanese Arabic " pego " or Arabic Jawi, which means todeviate. The final project delivers the theme "Arabic Pegon." in designing batik motifson casual clothing. The final assignment of this work the author wants to introduceand create very attractive casual clothing with Arabic Pegon designs that can fostergreater public appreciation and understanding of this script as part of Islamic historyand the richness of Indonesian culture. This uniqueness embodies creativity fordesigning works. The design of the work applies written batik techniques by applyingart design methods in the form of exploration, incubation, conceptualization, and materialization. The conclusion obtained is four batik motifs with Arabic Pegon ideas that are applied to casual clothing . The four clothing works are entitled Work 1 "Nurul Bainal Huruf", clothing 2 "Nourayya", clothing 3 "Mutri", clothing 4 "Mutika". With the existence of these four works, making Arabic Pegon letters as a source of ideas is expected to be better known by the wider community, and encourage Indonesian people to maintain Arabic Pegon letters as one of the cultural and historical heritages as well as a source of knowledge and classical literature.